Family Business: Typology development through 1980-2009 - Mayer-Granados, Elizabeth (Universidad Autónoma de Tamaulipas, 2012)
The family business is becoming increasingly important in the field of organizational research because of its distinctive features that influence its development, its importance in generating employment and contribution to national GDP, but also because its low survival rates when moving from one generation to another, making it necessary to look at it from different perspectives to understand this social phenomenon. Focusing the discussion on the substantial differences that distinguish family businesses among them the results of a careful review of the literature on nine different typologies that scholars have used to classify the same are presented. The results indicate that fifteen years it has prevailed one type of family business: the generational classifications, subsequently the researches has been focus on systems that comprise: business and family.